Unequal exchange: western economic logic and Inuit/Qablunaat research relationships. (13th December 2013) - Dutheil, April; Tester, Frank; Konek, Jordan
ABSTRACT: For some time, Inuit have made it clear that they wish to play a more substantial role in research with implications for themselves and their territory. To understand how researchers communicate and relate to each other, cultural analysis is often employed. Although cultural differences are relevant to understanding problems in the conduct of research, limiting differences to these realities is overly deterministic and essentialist. Many differences arising in the research process are products of social constructions found in Canadian culture and, increasingly, in Inuit communities. The paper re-examines the complexities of cross-class relations, focusing on how different relations to money, as a proxy for other relations characteristic of the capitalist mode of production, consumption and commodification, impact Inuit interaction with western-educated researchers. Using the Nanisiniq Arviat History Project in the community of Arviat, Nunavut Territory Canada, as a case study, the paper is a qualitative analysis of miscommunication resulting from cross-class differences. The Nanisiniq project was a two-year participatory action research project bringing Inuit youth and elders together to rediscover, interpret and apply knowledge of their history and culture to contemporary social issues affecting them.